2005
DOI: 10.1124/mol.105.012716
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-Induced Activation of Checkpoint Signaling Pathways That Affect Tumor Cell Survival

Abstract: Two signaling pathways are activated by antineoplastic therapies that damage DNA and stall replication. In one pathway, double-strand breaks activate ataxia-telangiectasia mutated kinase (ATM) and checkpoint kinase 2 (Chk2), two protein kinases that regulate apoptosis, cell-cycle arrest, and DNA repair. In the second pathway, other types of DNA lesions and replication stress activate the Rad9-Hus1-Rad1 complex and the protein kinases ataxia-telangiectasia mutated and Rad3-related kinase (ATR) and checkpoint ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
116
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 37 publications
9
116
0
Order By: Relevance
“…Chk2 depletion in gemcitabine-treated cells had no effect on entry into mitosis, in contrast to the premature entry into mitosis observed with Chk1 depletion (17). Finally, siRNA knockdown of ATR, ATM, or Chk1 led to sensitization of gemcitabine-treated cells, whereas Chk2 depletion had no effect (16).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Chk2 depletion in gemcitabine-treated cells had no effect on entry into mitosis, in contrast to the premature entry into mitosis observed with Chk1 depletion (17). Finally, siRNA knockdown of ATR, ATM, or Chk1 led to sensitization of gemcitabine-treated cells, whereas Chk2 depletion had no effect (16).…”
Section: Discussionmentioning
confidence: 65%
“…However, there is strong literature precedent indicating a major role for Chk1 versus Chk2 when both kinases were assessed simultaneously. For example, gemcitabine treatment activates both Chk1 and Chk2, but Chk1 to a greater extent as measured by phosphospecific antibodies (16,17). Additionally, both Chk1 and Chk2 can phosphorylate cdc25A, but in gemcitabine-treated cells only Chk1 siRNA knockdown resulted in stabilization of cdc25A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally thought of as a molecular sensor for double-strand breaks, the involvement of g-H2AX in recognizing other types of DNA damage and cellular stresses is becoming more evident (22, 33 -35). Whether H2AX is phosphorylated and forms nuclear foci at sites of nucleoside analogue -induced stalled replication forks has not been studied in detail (36).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] However, the effect of Chk1 inhibition on DNA-damage agents is dependent on the cell line and cytotoxic agent. [15][16][17][18][19][20] It has been reported that inhibition of Chk1 hyperactivated ataxia telangectasia mutated gene (ATM), Rad 3 related gene (ATR), and caspase-2 after γ-radiation and trigger a caspase-2-dependent apoptotic program in human tumor cells. 21 Our previous studies have showed that LDM induced alterations of Chk1 and Chk2 in various cancer cells, 22,23 but the potential effects of cell cycle checkpoint kinases on LDM cytotoxicity remain elusive.…”
Section: Introductionmentioning
confidence: 99%